Prognostic value of ABO blood group in patients with surgically resected colon cancer - Cao, X (Nature Publishing Group, 2014)
BACKGROUND: Previous studies supported a link between the ABO blood type and survival for several types of malignancies. Nonetheless, the relationship between ABO blood type and survival in colon cancer patients has not been rigorously evaluated. The goal of this retrospective analysis was to discern the correlations between ABO blood group and colon cancer survival. METHODS: A total of 1555 colon cancer patients that underwent curative-intent surgery between October 1995 and June 2002 were eligible for this study. The primary outcomes measured were the association between ABO blood group and patient survival. RESULTS: Compared with patients with non-AB blood types (blood types A, B, and O), patients with blood type AB were more likely to have better survival. The mean overall survival (OS) of the blood type AB patients was 113.9 months, whereas the mean OS of the non-AB blood type patients was significantly lower, 106.1 months (P<0.001, log-rank test). Compared with patients with blood type AB, the hazard ratios for patients with A, B, and O were 4.37 (95% confidence interval (95% CI), 2.65–7.20), 2.99 (95% CI, 1.81–4.96), and 2.78 (95% CI, 1.69–4.56), respectively. CONCLUSIONS: Blood type AB is a favourable prognostic factor for patients with colon cancer.